Luxury Brands in the Fashion industry on the Example of Dolce & Gabbana and Louis Vuitton - Abidogun, Boluwatife Fabiyi (Marki luksusowe w przemyśle modowym na przykładzie Dolce & Gabbana i Luis Vuitton, 2022)
The paper aims to examine how long-established luxury brands have been performing in the 21st century, identify their approaches to success, and gain knowledge about brand positioning using the example of Dolce & Gabbana and Louis Vuitton. The research me-thods used in this paper are the analysis of the literature on the subject, descriptive and comparative methods. One of the essential qualities a brand should have is keeping up with current trends, presenting innovations, and reaching new demographic groups while maintaining the demographics they started. The focus of this article is on the concept of a brand, its image, its equity, and how to measure them. It also covers the concept of luxury brands and thorough definitions of five distinct criteria: quality, authenticity, prestigious image, premium price command, and resonance. Components of a luxury brand are defined, with emphasis on the importance of price relevance to brand value in effect to brand perception and equity. Additionally, brand positioning, finding a position, and positioning mistakes often made by brands, as well as the role of gender in fashion to fully understand gender stereotyping in the industry and its effect on society are also discussed. The last area of focus is on understanding the two luxury fashion brands, their positioning, digital engagement, identity, consumer perception, expectation, and uniqueness. The conclusions drawn were based on the overall comparison between the two brands. Luxury brands are associated with high quality, authenticity, keeping an image of prestige, and premium prices. A damaged brand’s reputation degrades operating margins, cultural insensitivity can harm businesses and cause significant opportunities to be missed. Brands need to move along with trends or create new ones that appeal to the drivers of the sales market.
[w:] Ekonomia i międzynarodowe stosunki gospodarcze / pod red. Aleksandry Kuźmińskiej-Haberli. - Wrocław: Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2022, s. 49-58
Keywords: brand; positioning; logo; brand image; luxury fashion; consumer; campaign; Luis Vuitton; Dolce & Gabbana; marka; pozycjonowanie; wizerunek marki; moda luksusowa; konsument; kampania